Construct competition: historical-epistemological summary - Amadeo Cuba Esquivel (Pontificia Universidad Católica del Perú, 2016)
The aim of the article to demonstrate the necessity of a critical view on the construct of «competence» because of semantic and epistemic gaps. The analysis of the historical evolution of «competence» clarifies its origin and meanings. The epistemological analysis identifies the principle of efficiency as the basis of competence and also of programming and organization of educational process, based on this approach. The result of this double analysis highlights the intrinsic limits of the educational approach by competencies putting it in question.